Identification and typing of Yersinia enterocolitica and Yersinia pseudotuberculosis isolated from human clinical specimens in England between 2004 and 2018. Issue 4 (19th March 2019) - Hunter, Ebony; Greig, David R.; Schaefer, Ulf; Wright, Michael J.; Dallman, Timothy J.; McNally, Alan; Jenkins, Claire
Abstract : Purpose and Methodology . Epidemiological and microbiological data on Yersinia enterocolitica ( n =699) and Yersinia pseudotuberculosis ( n =35) isolated from human clinical specimens in England between April 2004 and March 2018 were reviewed. Traditional biochemical species identification and serological typing results were compared with species identifications and serotypes derived from whole-genome sequencing (WGS) data for a sub-set of these isolates ( n =179). Results. Most Y. enterocolitica isolates were from faecal specimens (74.4%) from adults (80.7%) and 50.7 % of isolates were from male patients. Most Y. pseudotuberculosis isolates were from blood cultures (68.6%) from adults (91%) and 60.0 % of isolates were from male patients. All sequenced isolates of Y. enterocolitica ( n =158) and Y. pseudotuberculosis ( n =21), as well as isolates belonging to other Yersinia species ( n =21), were correctly identified from genomic data using a kmer-based identification approach. Traditional phenotypic serotyping typed 82/158 and 12/21 isolates of Y. enterocolitica and Y. pseudotuberculosis, respectively, while 118/158 and 21/21 isolates of Y. enterocolitica and Y. pseudotuberculosis, respectively, were typed by the genome-derived serotyping method. In addition, WGS data provided a multi-locus sequence type profile and virulence gene profile for all isolates. Conclusion. The use of WGS for typing Y. enterocolitica and Y. pseudotuberculosis at Public Health England will facilitate the monitoring of animal-to-human transmission of these important foodborne pathogens in the UK and improve public health surveillance of the pathogenic lineages.